ETHNOMATHEMATICS: COCONUT SHELL CHARCOAL PRODUCTION PROCESS IN POND VILLAGE AND ITS IMPLEMENTATION IN MATHEMATICS LEARNING: ETNOMATEMATIKA: PROSES PRODUKSI ARANG BATOK KELAPA DI KAMPUNG KOLAM DAN IMPLEMENTASINYA DALAM PEMBELAJARAN MATEMATIKA - Yolanda, Putri; Ginting, Siti Salamah Br (MaPan : Jurnal Matematika dan Pembelajaran, 2023)
The purpose of this study is to reveal and implement mathematics learning with community activities. This research focuses on the production process of charcoal handicrafts derived from coconut shells by communities in Kampung Kolam, Deli Serdang, North Sumatra. This research uses qualitative research methods with an ethnographic approach. The method of data collection in this study is by observation, interviews, and documentation. This research instrument is the researcher himself who is supported by observation sheets, interview sheets, stationery, and documentation tools. Data analysis techniques used in this study are data reduction, data presentation, and conclusions. While the data validity technique in this study uses triangulation techniques, namely by comparing data based on observations, interviews, and documentation. The results of the study show that there is a mathematical concept in the coconut shell charcoal production process, namely build a curved side space contained in a hollow hemispherical coconut shell and a tubular kiln used, build a flat side space contained in the block-shaped kiln used, a comparison of the value and reverse value contained in time and the number of coconut shells used.